Lichen planus pigmentosus inversus - Metin, Zuhal; Kapiskay, Deniz; Durmaz, Koray (Dermatology Review/Przegląd Dermatologiczny, 2022)
Lichen planus pigmentosus inversus is a rare subtype of lichen planus and can be seen with or without lichen planus lesions. Dark brown, gray-colored reticular macules and patches are mainly present in intertriginous areas. Although T cell-mediated autoimmunity has been implicated in the etiopathogenesis of the disease, it has not been elucidated. Here, we present a 48-year-old man with lichen planus pigmentosus inversus and type 2 diabetes. The diagnosis of the disease which was established based on clinical appearance and histopathology. Other reported cases of lichen planus pigmentosus are also discussed.